(untitled) (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
Vilém Flusser uses the concept of illusion in a non-systematic way, resulting in two ostensible contradictions. First of all, he often uses the term illusion, while criticizing the metaphysic assumptions that it implies; secondly, he seems to both dispraise and value the illusionary nature of technical images. This article aims at clarifying Flusser’s thoughts on illusion in the belief that they are not as conflicting as they might seem at first. In fact, when Flusser deplores the risk of deception associated with technical images, he refers to the illusion of transparency. He does not oppose the concept of illusion to a supposed objective truth, on the contrary, he opposes the illusion of the objective nature of images to the awareness of their constructed and mediated character. However, a rational demystification of illusions is not a viable option, since, according to Flusser, they are the result of a voluntary self-deception: we suppress our critical thinking because we cannot bear its complexity, we want images to “release us from the necessity for conceptual, explanatory thought.” This is why Flusser thinks that aware illusion – in other words: fiction – can help us overcome our “inertia of happiness” and develop a critical imagination.